Respuesta :

Answer:

x = 0 or [tex]x = \frac{17}{3}[/tex]

Step-by-step explanation:

We have the quadratic equation of variable x and we have to solve the equation using the square root property.

Now, we have x(3x - 17) = 0

⇒ 3x² - 17x = 0

⇒ [tex]3(x^{2}  - \frac{17}{3}x ) = 0[/tex]

⇒ [tex]x^{2} - 2 \times (\frac{17}{6}) \times x + (\frac{17}{6} )^{2} = (\frac{17}{6} )^{2}[/tex]

⇒ [tex](x - \frac{17}{6})^{2} = (\frac{17}{6} )^{2}[/tex]

Now,square rooting both sides we get,  

[tex]x - \frac{17}{6} = \pm\frac{17}{6}[/tex]

Therefore, either x = 0 or [tex]x = \frac{17}{3}[/tex] (Answer)

ACCESS MORE